2015
DOI: 10.1002/ange.201504494
|View full text |Cite
|
Sign up to set email alerts
|

SiSi Double Bonds: Synthesis of an NHC‐Stabilized Disilavinylidene

Abstract: An efficient two-step synthesis of the first NHCstabilized disilavinylidene (Z)-(SIdipp)Si = Si(Br)Tbb (2; SIdipp = C[N(C 6 H 3 -2,6-iPr 2 )CH 2 ] 2 ,T bb = C 6 H 2 -2,6-[CH-(SiMe 3 ) 2 ] 2 -4-tBu, NHC = N-heterocyclic carbene) is reported. The first step of the procedure involved a2 :1 reaction of SiBr 2 (SIdipp) with the 1,2-dibromodisilene (E)-Tbb(Br)Si = Si(Br)Tbba t1 00 8 8C, whicha fforded selectively an unprecedented NHC-stabilized bromo(silyl)silylene,n amely SiBr-(SiBr 2 Tbb)(SIdipp) (1). Alternativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 78 publications
1
13
0
Order By: Relevance
“…[8c] In digermavinylidene (33), the four atoms that defined the B 2 GeGe unit, lied within a single plane. The structural analysis of 33 revealed the presence of weak interaction between flanking arene π systems (aryl rings of each of the boryl ligands) and vacant in-plan p orbital at Ge2, confirmed by variable-temper- 2.167(2) C SIdipp À Si2À Si1: 97.6(1)° [16] 2.4716(11) Si2À Si1À Si2*: 115.09(3)° [24] 2.223 17B1À Si1À Si2: 127.34 14°, B2À Si2À Si1: 128.20 14° [ 27] Scheme 13. General synthetic methods for digermene: a) photolysis or ring opening of cyclotrigermanes, [31,32a] b) reductive dehalogenation [31,32b-d] and c) dimerization.…”
Section: Digermenes (> Ge=gementioning
confidence: 95%
See 3 more Smart Citations
“…[8c] In digermavinylidene (33), the four atoms that defined the B 2 GeGe unit, lied within a single plane. The structural analysis of 33 revealed the presence of weak interaction between flanking arene π systems (aryl rings of each of the boryl ligands) and vacant in-plan p orbital at Ge2, confirmed by variable-temper- 2.167(2) C SIdipp À Si2À Si1: 97.6(1)° [16] 2.4716(11) Si2À Si1À Si2*: 115.09(3)° [24] 2.223 17B1À Si1À Si2: 127.34 14°, B2À Si2À Si1: 128.20 14° [ 27] Scheme 13. General synthetic methods for digermene: a) photolysis or ring opening of cyclotrigermanes, [31,32a] b) reductive dehalogenation [31,32b-d] and c) dimerization.…”
Section: Digermenes (> Ge=gementioning
confidence: 95%
“…DFT studies revealed cyclic delocalization of six mobile electrons of the π-, σand non-bonding type across the central four-membered ring. The reduction and isomerization studies of the dismutational isomer of the hexasilabenzene (16) was carried out by Scheschkewitz and co-workers. [23h-j] Recently, Iwamoto and Ishida et al synthesized a tetrasilicon compound (18), analogue of bicyclo [1.1.0]but-1(3)-ene, having a formal double bond between bridgehead silicon atoms.…”
Section: Disilenes (> Si=simentioning
confidence: 99%
See 2 more Smart Citations
“…Tw oa lternative mechanisms can be considered:1)the direct silylene insertion into aS i À Xb ond (X = H, Cl) of as econd monomer;o r2 )atwostep process involving the first formation of disilenes 4 followed by a1 ,2-migration of substituent X. [16,17] However, all attempts to find ar eaction pathway leading to disilenes 4 failed, even though dimers 4 are aminimum on the potential energy surface,a nd the dimerization process is only slightly endergonic in the case of 2a-H (DG 1 = 12.6 kJ mol À1 ). The formation of 4b-Cl is more endergonic (DG 1 = 66.9 kJ mol À1 ), which is probably due to steric reasons.Itisimportant to note that the optimized geometries of 4a,b reveal that they can be regarded as silylenes stabilized by as econd silylene ligand, rather than symmetric disilene structures (Figure 4).…”
Section: Methodsmentioning
confidence: 99%